Penggunaan Anggah Ungguhing Basa Bali: Sebuah Kesantunan dan Penanda Kelas Sosial Masyarakat Bali - Duana Sutika, I Nyoman (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 19 No 2 (2019), 2019)
Balinese language with its leveling still intensively used by the Balinese people. Anggah-ungguhing basa (the languages levels) mostly used in the traditional event, and in special events, such as a workshop, conference, and seminars. It also used when the Balinese communicate with elder and strangers. Generally for most Balinese language regarded as the mother language, especially those who live in rural areas.Since the lack of young generation interest, the use of Balinese language levels has decreased.Intead of complicated language levels in Balinese, the young Balinese prefer to use Indonesian, as its more practical and easier.On the other hand, the Balinese language levels, contain a value of modesty, courtesy, and manners, also be a symbol of social class in Balinese society. Communication is arranged based on a social class using fine andcoarse language.